Historical linguistics and endangered languages exploring diversity in language change - Law, Danny 1980; Pat-El, Na'ama (Routledge studies in historical linguistics, 2022)
"This collection showcases the contributions of the study of endangered and understudied languages to historical linguistic analysis and the broader relevance of diachronic approaches toward developing better informed approaches to language documentation and description. Bringing together perspectives from both established and up-and-coming scholars representing a globally and linguistically diverse range of languages, the volume demonstrates the ways in which endangered languages have and can challenge existing models of language change based around standard languages and generate innovative insights into linguistic phenomena, including pathways of grammaticalization, forms and dynamics of contact-drive change, and the diachronic relationship between lexical and grammatical categories. In so doing, the book highlights the notion that processes of language change long held to be universal are in fact shaped by cultural and typological variability. Taken together, this collection brings together perspectives from language documentation and historical linguistics toward pointing the way forward for richer understandings of language change and documentation and description, making this key reading for scholars in these fields"--